2014
DOI: 10.1155/2014/308270
|View full text |Cite
|
Sign up to set email alerts
|

Management of Superficial Abscesses: Scope for Day Case Surgery

Abstract: Background. Patients presenting with superficial abscesses are often regarded as low priority and given a less efficient service. Aim. The aim of this study was to investigate the efficiency of emergency treatment of superficial abscesses and to identify areas for service improvement. Method. A retrospective case review of patients admitted to Derriford Hospital, Plymouth, over a four-month period. Results. Ninety-seven patients were included in the study. Seventy two (74%) arrived between 08.00 and 16.00 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In this study, perianal abscess accounted for the majority of abscesses followed by pilonidal abscesses, both of which accounted for about a quarter each of the types of abscesses treated. Nixon et al, in another UK study, found pilonidal abscess was the most common cause in their study [6]. Pyrexia, WCC, and CRP level serve as readily available objective parameters for assessing the severity of the infection and provide clinicians with guidance during the care of patients presenting with an infection [7,8] Majority of the patients in this study did not demonstrate signs of severe infection and were well enough for a deferment of their treatment till the next day.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, perianal abscess accounted for the majority of abscesses followed by pilonidal abscesses, both of which accounted for about a quarter each of the types of abscesses treated. Nixon et al, in another UK study, found pilonidal abscess was the most common cause in their study [6]. Pyrexia, WCC, and CRP level serve as readily available objective parameters for assessing the severity of the infection and provide clinicians with guidance during the care of patients presenting with an infection [7,8] Majority of the patients in this study did not demonstrate signs of severe infection and were well enough for a deferment of their treatment till the next day.…”
Section: Discussionmentioning
confidence: 72%
“…This would have allowed discharge home at presentation to the hospital and planned hospital attendance on the next morning for incision and drainage. Ambulatory care uniquely conserves scarce hospital resources and provides a safe, effective, and more convenient care pathway for the patient with a significantly better overall patient experience than would be obtained from prolonged inpatient hospital wait for their procedure [6]. Our pathway provides clinicians with a guide to harnessing the numerous benefits to the patients and the hospital inherent in this approach to service provision.…”
Section: Discussionmentioning
confidence: 99%
“…The case for managing superficial abscesses as ambulatory cases was made as early as 1997, 5 with subsequent retrospective studies suggesting it could be offered in 60–90% of cases 6–8 . Implementation of day‐only surgery programs typically require anaesthetic expertise, staff education, appropriate patient counselling, and protected theatre time 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The case for managing superficial abscesses as ambulatory cases was made as early as 1997, 5 with subsequent retrospective studies suggesting it could be offered in 60-90% of cases. [6][7][8] Implementation of day-only surgery programs typically require anaesthetic expertise, staff education, appropriate patient counselling, and protected theatre time. 9 Early efforts were often individual or teamdriven rather than designed as specific programs, 1 which is unsustainable given constant staff rotation in Australian public hospital surgical units.…”
Section: Introductionmentioning
confidence: 99%